A SEMANTIC-PRAGMATIC ANALYSIS OF COLOR-RELATED PROVERBS IN ENGLISH, KAZAKH, AND UZBEK - Mamaniyazova Nodira Saydullayevna; Tagayeva Umida Ernazarovna; Ruziyeva Umida Abruykul kizi (Web of Journals Publishing, 2025)
This paper explores the semantic and pragmatic dimensions of color-related proverbs in English, Kazakh, and Uzbek. As repositories of collective wisdom, proverbs are shaped by cultural experience and worldview, often embedding symbolic elements such as color. By analyzing selected proverbs, the study highlights how similar colors convey divergent meanings and perform various pragmatic functions across languages. The analysis reveals both cross-linguistic parallels and culturally specific interpretations.
Keywords: Color symbolism, cross-cultural pragmatics, proverbs, semantics, English, Kazakh, Uzbek, language and culture.